Pengembangan Model Pelatihan PTK Berbasis Pendampingan untuk Meningkatkan Profesionalitas Guru Matematika SMA di Kabupaten Brebes - Masrukhi, Masrukhi; Widodo, Joko; Sukestiyarno, Sukestiyarno; Raharjo, Tri Joko (Muhammadiyah University Press, 2015)
Classroom-based Â action research (CAR) for high school math teachers is very important to develop their professionalism.Â To improve the competence of teachers, a development of CAR Â training Â model Â based Â on Â mentoring Â isÂ needed. Â This Â study Â aims Â to Â produce Â an appropriate Â CAR Â training Â model Â based Â on Â mentoring Â toÂ improve Â teachersâ professionalism.Â This study employed research and development (R & D) model, then the procedure pursued in this research started from Â (1) literature study, (2) preliminary field study, Â (3)Â needs Â analysis, Â (4) Â preparing Â theÂ training Â model Â design, Â (5) Â performing validation model, (6) revising the model, (7) preparing hypothetical model of training, (8) performing limited testing and expanded trials, and (9) revising the final model through the Â focus Â group Â discussionÂ Â (FGD-2), Â experts, Â and Â practitionersÂ Â to Â obtain Â the Â final model.TheÂ Â resultÂ Â showsÂ Â that: Â (1) Â the Â productÂ Â whichÂ Â is Â validatedÂ Â by Â expertsÂ Â and practitioners Â obtains Â a mean Â score Â of 62.15 Â (good Â qualification), Â (2) the finalÂ training model is very feasible to be used by the indication of the its mean score at 3.59 (very high) for its usefulness, the mean score of 3.48 (very high) for its practicality, the mean score of3.58 Â (very Â high) Â for Â its Â feasibility. Â The Â implementationÂ Â of Â training Â program Â is Â alsocapable of producingÂ CAR research reports. The conclusions Â of research is that the final model of CAR training based on mentoring and its training instruments are very feasible to be used to improve the professionalism Â of senior high school math teachers in Brebes.